POTENSI BAKTERI ENDOGEN DALAM MEMINIMALISIR SENYAWA AMONIA DI SUNGAI KALIOTIK LAMONGAN - Megasari, Miatri; Sulistiono, Eko; Syakbanah, Nur Lathifah; Prasidya, Denaya Andrya (Universitas Ahmad Dahlan, 2023)
The Kaliotic River is the water that flows in several villages in the Lamongan area. The Kaliotic River is a stream of water that is used as a disposal site for liquid waste left over from agriculture and leftover fish markets. The condition of the Kaliotic river which is used as a garbage disposal site is the basis of this research. This research was conducted with the aim of analyzing the potential of endogenous bacteria in the degradation of Kaliotic river waste. Based on the problems that exist in the Kaliotic river, this research was conducted using a quantitative descriptive method and using a true experimental method. Based on the isolation results, isolates were produced, namely isolates suspected to be ammonia degrading bacteria (bacteria A). Ammonia levels also decreased at point 1 by 17.6%; at the 23.3% point; and at point 3 that is 16.21%. The results of the bacterial potency test using a bacterial isolate concentration of 2% each and 98% water sample and can minimize ammonia compounds but do not comply with quality standards.